Two new erythroneurine leafhopper genera and first record of Thailus Mahmood from China (Hemiptera: Cicadellidae: Typhlocybinae), with description of four new species - Cao, Yanghui; Zhang, Yalin (Zootaxa, 2013)
Two new genera of tribe Erythroneurini from China, Saccata gen. nov. and Variolosa gen. nov. are described and illustrated based on type species Saccata insolita sp. nov. and Variolosa meni sp. nov. respectively. Genus Thailus Mahmood with new species Thailus versicolor sp. nov. is reported from China for the first time and another new species, T. rectilinea sp. nov. from Thailand is also described. A key to adult males of Thailus is provided.